2011
DOI: 10.1302/0301-620x.93b4.25449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-intensity pulsed ultrasound stimulation on callus remodelling in a gap-healing model

Abstract: We evaluated the effect of low-intensity pulsed ultrasound stimulation (LIPUS) on the remodelling of callus in a rabbit gap-healing model by bone morphometric analyses using three-dimensional quantitative micro-CT. A tibial osteotomy with a 2 mm gap was immobilised by rigid external fixation and LIPUS was applied using active translucent devices. A control group had sham inactive transducers applied. A region of interest of micro-CT was set at the centre of the osteotomy gap with a width of 1 mm. The morphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Ossification of the maxillofacial bones is intramembranous, whereas in the long bones ossification is endochondral. 16 Some studies concerning the efficacy of LIPU on maxillofacial bone are in favour of its use. El-Bialy et al reported a significantly positive effect of LIPU on mandibular bone regeneration in distraction osteogenesis in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Ossification of the maxillofacial bones is intramembranous, whereas in the long bones ossification is endochondral. 16 Some studies concerning the efficacy of LIPU on maxillofacial bone are in favour of its use. El-Bialy et al reported a significantly positive effect of LIPU on mandibular bone regeneration in distraction osteogenesis in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not clear that LIPUS stimulates bone regeneration in the maxillofacial area because regenerative process of a bone commonly generally follows its embryological process. Bones in the maxillofacial area are flat and formed by intramembranous ossification whereas most bones in other parts of the body are long bones and produced by endochondral ossification [11]. It has been recently reported that LIPUS also stimulates bone regeneration in calvaria bone defects in rats [5,12].…”
Section: Open Accessmentioning
confidence: 99%
“…It has been proved that LIPUS can promote formation of the medullary canal and cortex in a gap-healing model, which then leads to earlier restoration of the structural integrity of the healing site 11 . Many clinical studies indicate that LIPUS can enhance the healing of fresh fractures, delayed unions, nonunions, distraction osteogenesis and congenital pseudoarthroses 7,8,12,13 .…”
Section: Introductionmentioning
confidence: 99%